Effect of supplementary feeding on honeybee colonies performance in Wag-Lasta area, North-Eastern Ethiopia - Girmay, Ayalew; Lema, Meresa; Tsegaye, Alemu; Ebrahim, Yesuf; Desale, Ertiban (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Honey bees need pollen and nectar to survive, and strong colonies before colony buildup season require proper feeding to support brood development. This study evaluated the impacts of supplements with varying protein content on colony performance, brood rearing, and honey production. Sixteen colonies were divided into four groups: three treatments and one control, each with four replicates. Treatments included Acacia pod flour: pollen (9:1 w/w), pea flour: pollen (9:1 w/w), and a mix of Acacia pod and pea flour: pollen (9:1 w/w); the control group received no supplementation. Feed was given in feeder supper box hives and measured every 7 days, with intake and refusal recorded. Hive resources such as pollen, nectar, brood space (cm2), adult bees, and honey were assessed using a frame-sized grid meter at the Gazgibilla apiary research site. Feed types were selected through palatability testing. The mixture of Acacia pod and pea flour had the highest consumption (243.19 g/day), brood area, pollen area, nectar area, colony size (frames covered with bees), and honey yield (35 kg/colony). The control group had the lowest values on all measures. Supplementary feeding increased honeybee populations and improved colony performance during dearth periods. The author recommends the commercial use of the Acacia and pea diet mix for sustained colony growth during the dearth periods.